Perlindungan Hukum Konsumen Air Minum Isi Ulang Pada Masyarakat Umum - Dwi Atmoko; Noviriska (Journal of Mandalika Literature, 2025)
The obstacle for consumers of refill drinking water to obtain legal protection is the low level of legal awareness for refill drinking water business actors regarding the obligation of business actors to provide correct and honest information regarding the conditions and guarantees regarding the refill drinking water they sell. Apart from that, another obstacle for consumers is that consumers do not know about the rights they have and consumers do not know where to complain and demand responsibility for the losses they experience, which is why many consumers do not get legal protection. Consumer rights are related to consumption. Drinking water refills are not working well. Refill drinking water depots do not provide information to consumers about the condition of refill drinking water, namely information about hygiene, valid registration marks, laboratory inspection results regarding the quality of refill drinking water. Business actors have violated the UUPK regarding consumer rights by not providing clear, honest and correct information to consumers. Business actors have a tendency to "harass" consumer rights and take advantage of consumer weaknesses without having to receive legal sanctions. Business actors have the freedom to produce commodities, without having to follow applicable standards. They do not need to compensate for losses experienced by consumers as a result of purchasing/consuming products. which is not quality. Business actors are quite free to promote products, by tricking or taking advantage of consumers' ignorance about the product. There is a need for strict sanctions against naughty business actors as regulated in Law Number 8 concerning Consumer Protection so that there are no more violations in the sale of drinking water.